Karakter Youkai dalam Game Onmyoji Arena - Hismubaroq, Yukaido; Laksmita Sari, Ida Ayu; Oeinada, I Gede (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 23 No 2 (2023), 2023)
This research is titled "Youkai Characters in Onmyoji Arena Game". This research aims to describe the depiction of youkai used as characters in the Onmyoji Arena game. The method used in this research is descriptive analysis method. This research uses semiotics theory according to Charles Sanders Peirce. Based on the research results, there are five youkai taken in the Onmyoji Arena game. The depiction of the form of youkai contained in the Onmyoji Arena game has several things related to the concept of youkai in Japanese beliefs. The depictions seen in the youkai in the Onmyoji Arena game are (1) Youkai Tanuki who is related to sake and the science of shapeshifting. (2) Youkai Zashiki Warashi which is related to luck and house guardian spirits. (3) Youkai Yumekui who likes to eat dreams. (4) Youkai Kiyohime who has a tragic love. (5) Youkai Aoandon who is related to the event 'Hyakumonogatari Kaidankai'. These five youkai produce icons, indexes, and symbols. The icon is an image, the index is the emergence of the youkai, and the symbol is the meaning of the youkai in Japanese society.